An Assiduous Study on the Viability of Organic products in Delhi and NCR Region - Ms. Sakshee Singh, Dr. Garima Malik, Dr. Arun Bhatia (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
A variety of organic products are available in the domestic market such as cosmetics like skin moisturizers, perfumes, lipsticks, fingernail polishes, makeup, shampoos, permanent waves, hair colors, toothpastes, and deodorants,anti-dandruff shampoos and antiperspirant-deodorants, as well as moisturizers and makeup with SPF (sun protection factor) numbers, besides tea, coffee, rice, wheat, pulses etc. Products which are available for export market, besides these, include but not limited to, are, cashew nuts, cotton, oil seeds, various fruits and medicinal herbs. The presence of wholesalers and traders, distributors, retailers, shopping malls,super markets and mom and pop shops are the major channels available in the domestic market and accounts for only 12.5 per cent of the total organic production. However, from the study of Delhi and NCR region of the Country , the markets and shops for organic products are slowly and steadily coming up , owing to the fact that many of the consumers mainly working and non working women, who are the driving force in the purchase of organic products, are realizing the need and importance of using the organic products rather than non-organic products.This leads to a crucial importance to study the viability of organic products and its growth and development in terms of its market share